Pengaruh Emotional Exhaustion terhadap Hubungan Antara Psychological Contract Breach dan Turnover Intention pada Karyawan Perusahaan Edukasi Digital di Jakarta - Iffan Aviananda Perdanaputra; Andreas Wahyu Gunawan Putra (J-MAS (Jurnal Manajemen dan Sains), 2022)
Changes, especially in the Postpandemic era, can bring new opportunities and problems to businesses and organizations. These changes can trigger Psychological Contract Breach, which if left unsolved can end up with Turnover Intention of employees. The presence of Emotional Exhaustion experienced can also worsen the situation at work. This study aims to analyze the effect of Emotional Exhaustion as an intervening variable on the relationship between Psychological Contract Breach and Turnover Intention on employees of a digital education company in Jakarta. This study used a questionnaire survey to collect data to test research hypotheses. The type of research used is quantitative, with the PLS-Structural Equation Modeling (SEM). The research sample selected using the purposive sampling method was 200 employees of a digital education company in Jakarta. Psychological contract breach on emotional exhaustion; emotional exhaustion on turnover intention; psychological contract breach on turnover intention ; psychological contract breach on turnover intention through emotional exhaustion.